Corrosion Behavior Of Quenched SAC305 Solders - Muhamad, Nor Syafiqah (Universiti Sains Malaysia, 2018)
The effect of corrosion behavior of quenched SAC305 solder alloy with different cooling methods such as furnace cooled and ice quenched were investigated. Typical phases present in SAC305 solder with different cooling methods were β-Sn, Ag3Sn and Cu6Sn5. The microstructure of furnace cooled was coarser than microstructure of ice quenched. The thickness of IMC layer was thicker (4.558 μm) for furnace cooled and thinner (1.532 μm) for ice quenched. The growth of Sn and eutectic phases were longer for furnace cooled and has limited time for ice quenched. The corrosion behavior of different cooling methods was investigated in 3.5 wt% NaCl solution by open circuit potential (OCP) and potentiodynamic polarization. Based on potentiodynamic polarization curve, ice quenching exhibit larger passivation range and lower passivation current density indicates more stable and protective passive layer. Phases, morphologies and elemental analysis were used to characterize the sample of SAC305 solder at different cooling rate. In addition, the microstructural and elemental analysis revealed the presence of oxide on the surface of the corroded sample. The grain size of corrosion product in furnace cooled sample was larger and the oxide form was large plate-like shape as compared to ice quenched sample that has a uniform and small plate-like shape. Results showed that ice quenched sample exhibits better corrosion resistance than furnace cooled sample due to compact corrosion product layer that can protect the surface of the SAC305 solder alloy.